2018
DOI: 10.1080/15376516.2018.1440679
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic induces cardiac rhythm dysfunction and acylcarnitines metabolism perturbation in rats

Abstract: This study provides information concerning the effect of arsenic at different concentrations on cardiac rhythm (such as QT, QTc, and heart rate) but not on cardiac cycle length. The metabolism of acylcarnitine metabolites can be a potential pathway for arsenic-induced cardiac rhythm dysfunction in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Arsenic exposure is known to induce the hyper phosphorylation of protein tau [27], and increase the production of amyloid-β [28], both of which are involved in the formation of neurofibrillary tangles and brain amyloid plaques [29]. Arsenic is a well-known cardiovascular toxicant that causes cardiovascular diseases [30,31], which is in agreement with the vascular hypothesis of AD. The current vascular hypothesis of AD proposes that the AD is the result of vascular damages which reduces the cerebral blood perfusion rate and therefore indirectly impairs neuron [32,33].…”
Section: Discussionmentioning
confidence: 66%
“…Arsenic exposure is known to induce the hyper phosphorylation of protein tau [27], and increase the production of amyloid-β [28], both of which are involved in the formation of neurofibrillary tangles and brain amyloid plaques [29]. Arsenic is a well-known cardiovascular toxicant that causes cardiovascular diseases [30,31], which is in agreement with the vascular hypothesis of AD. The current vascular hypothesis of AD proposes that the AD is the result of vascular damages which reduces the cerebral blood perfusion rate and therefore indirectly impairs neuron [32,33].…”
Section: Discussionmentioning
confidence: 66%
“…Our study has confirmed the prolongation of QT interval as a major complication of As exposure. [40][41][42] Blocking potassium channels by As increases the risk of excessive repolarization delay in phase 3 of the cardiac action potential, causing changes in ventricular action potential duration (APD). 43 Increased APD is reflected by prolongation of the QT interval, displaying ventricular depolarization and repolarization.…”
Section: Discussionmentioning
confidence: 99%
“…Arsenic is an ancient toxic metal that is commonly found in the environment. NaAsO2 is the most toxic, affecting people in many countries around the world, including China.Arsenic has been shown to cause many cardiovascular diseases and to cause cardiomyocyte damage and cardiomyocyte apoptosis 5,6) .Sodium tanshinone IIA sulfonate (STS) has been approved by China Food and Drug Administration (CFDA) for the treatment of cardiovascular disease. 7,8) However, the combination of NaAsO2 poisoning and STS has not been reported.…”
Section: Discussionmentioning
confidence: 99%